ABORDAJE QUIRURGICO DEL QUISTE GLOBULOMAXILAR - Palacios A., Elmo (1999)
Is defined and clasifiqued the Globular Cyst of Maxillary, indicating the controversy about your etiology and describe the thecnics for the surgical treatment. Finally to introduce a clinical case. Your treatment is realiced in the Nationald University of San Marcos School of Dentistry Department ofthe Oral and Facial Maxillary Surgery, in Lima•Perú.